2017
DOI: 10.1177/1179544117733446
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Atlas Unicompartmental Knee System Load Absorber in Improving Pain Relief and Function in Patients Needing Unloading of the Medial Compartment of the Knee: 1-Year Follow-Up of a Prospective, Multicenter, Single-Arm Pilot Study (PHANTOM High Flex Trial)

Abstract: In young patients with medial knee osteoarthritis (OA), surgical intervention may not be desirable due to preferences to avoid bone cutting procedures, return to high activity levels, and prolong implant survival. The Atlas Knee System was designed to fill the gap between ineffective conservative treatments and invasive surgery. This single-arm study included 26 patients, aged 25 to 65 years, who completed 12 months of follow-up. All dimensions of the Knee injury and Osteoarthritis Outcome Score (KOOS), Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 34 publications
1
22
0
3
Order By: Relevance
“…The reduced levels of medial and lateral compartment stress indicate the potential for pain relief and improved function in patients with knee OA. These notions were supported by the clinically observed improvements in pain and function of patients implanted with the Atlas™ …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reduced levels of medial and lateral compartment stress indicate the potential for pain relief and improved function in patients with knee OA. These notions were supported by the clinically observed improvements in pain and function of patients implanted with the Atlas™ …”
Section: Discussionmentioning
confidence: 99%
“…As the knee moves into swing phase, the piston and absorber will separate until the device becomes disengaged to maintain a smooth gait pattern. 5 Slynarski et al demonstrated improved pain and function in patients with medial knee OA after implantation of the Atlas™. At 12-month follow-up, Knee Osteoarthritis Outcome Scores (KOOS) for pain improved by 35 points from 44 ± 2 to 79 ± 4, and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain by 37 points from 54 ± 2 to 16 ± 4.…”
mentioning
confidence: 99%
See 3 more Smart Citations